Chaetocladius Kieffer (Diptera: Chironomidae) in China - Wang, Qian; Kong, Fanqing; Wang, Xinhua (Entomologica Fennica, 2012)
Chaetocladius Kieffer in China is reviewed and a key to the males is provided. There are five Chinese species, of which three are described and illustrated as adultmales: C. absolutus Wang, Kong & Wang, sp. n., C. tibetensis Wang, Kong & Wang, sp. n. and C. triquetrus Wang, Kong & Wang, sp. n. Chaetocladius oyabevenustus Sasa, Kawai & Ueno is recorded from China for the first time.